Effectiveness of Modified Tension Band Wiring for Medial Mallelous Fracture of Tibia - KC, Dipendra; Shrestha, Dinesh Kumar; Karki, Prateek; Yogi, Sushil (Journal of Nepalgunj Medical College, 2021)
Introduction: Medial malleolus fracture is one of the commonest fractures. Non-operative approach may fail to produce anatomical reduction leading to ankle instability, nonunion and post traumatic osteoarthritis of the ankle. Proper anatomical reduction and stable internal fixation remains the key in treatment of displaced fracture. Good result had been achieved with Modified Tension Band Wiring. Aims:The purpose of our study was to evaluate the functional outcome of medial malleolus fracture treated with modified tension band wiring. Methods:This prospective observational study was conducted in department of Orthopaedics of Nepalgunj Medical College and Teaching Hospital from September 2018 to August 2021. Patients were evaluated for mode of injury, type of fracture, associated injury, radiological union, functional outcome, accompanying complications. All of the medial malleolus fractures in this study were treated by modified tension band wiring and outcomes were evaluated using Olerud and Molander Score. Results: In this study of 40 patients with the mean age of 41.60+13.75 year, 31(77.5%) were male and 9 (22.5%) were female. Majority of fractures were observed between 35 to 44 years, right side was predominantly involved, road traffic accident was the most common mode of injury. The average time duration of surgery from the time of injury was 5.25 days. Final functional outcome as per Olerud and Molander score showed, seven (17.5%) patients had excellent results, 30 (75%) patients had good results and three (7.5%) patients had poor results. The most common complication noted was hardware prominence at 7.5%, followed by superficial wound infection in 5% of patients. Conclusion: Modified Tension band wiring of medial malleolus results in good to excellent outcome in most of the patients with few complications .